Out of the Library and on to the Floors: Librarian Participation in Nursing Rounds. Issue 3 (2nd July 2016) - Hargwood, Pamela; Duffy, Christopher
ABSTRACT: Physicians, nurses, residents, pharmacists and social workers are commonly thought to be part of the healthcare team. Incorporating medical librarians as part of this team is beneficial not only to the library patrons, but to the library as well. Nurses are often asked to respond immediately to clinical care questions. However, they do not always have the time or resources available. This article describes the successful implementation of a collaborative librarian rounding service provided by two librarians from separate institutions; an academic medical center library and a hospital library.